Os Serviços de água e esgoto no estado do Rio de Janeiro: Regulação e privatização (GEOgraphia, 2009)
Este  artigo  explora as  contradições do  novo modelo institucional no  Brasil, cuja  implementação vem  provocando mudanças significativas na  posição  dos municípios no  que diz  respeito ao controle dos serviços de  água e saneamento. A partir  da  Lei 9.433197,  analisa-se as  adaptações  dos municípios  ao  novo  quadro  institucional. Argumenta-se que as mudanças propostas não garantem a competitividade na indústria de água e saneamento, pressuposto dos marcos regulatórios vigentes.Abstract:This paper explores  the contradictions in  the new model  of the water regulation  in Brazil, which  result  in a reconfiguration of  the position of  the municipalities  in the water  industry. We  briefly outline the main  changes introduced by  the 9433 Law  (Water Law) and  analyze how the municipalities are adjusting  themselves  to  this new order. The changes  in  the  Rio  de  Janeiro water  industry provide  an  example  in  which  institutional shifts are no guarantees  to produce competitiveness in  the water industry.